Business and professional communication : keys for workplace excellence - Quintanilla, Kelly M., ....-; Wahl, Shawn T., ....- (Los Angeles : SAGE, 2017)
Professional success requires excellent communication skills. Organized around the transition from student to professional life, Business and Professional Communication, Third Edition gives readers the tools they need to move from interview candidate to team member to leader. Kelly M. Quintanilla and Shawn T. Wahl help students understand the role communication plays when successfully handling situations like job interviewing, providing feedback to supervisors, and working in teams. The fully updated Third Edition includes expanded coverage of making competent choices in new communication channels, increased emphasis on skill building for business writing and presentations, and the effective use of visual aids.
Includes bibliographical references (pages 345-354) and index.
Keywords: Business communication